Advances in the development of rice varieties with better nutritional quality in Indonesia - Sitaresmi, Trias; Hairmansis, Aris; Widyastuti, Yuni; Susanto, Untung; Wibo, Bayu Pramono; Widiastuti, Mira Landep; Rumanti, Indrastuti Apri; Suwarno, Willy Bayuardi; Nugraha, Yudhistira (Elsevier, 2023)
Rice is the major food crop in Indonesia, and its consumption is still considerably high, indicating that daily nutrient uptake relies on its grain. An unbalanced diet leads to some health problems in Indonesia, such as stunting, anemia, and diabetes. Increasing the nutritional value of rice through crop improvement is an important strategy for reducing the prevalence of malnutrition. Improvement of the nutritional qualities of rice varieties has been achieved by developing antioxidant-rich pigmented rice, micronutrient-rich rice, and low glycemic index (GI) rice varieties. Pigmented rice varieties have been released for farmer adoption in Indonesia, either with red or black aleurone. Improvement of the micronutrient content of rice through a cross-breeding approach has been successful for zinc. High-zinc rice varieties for different rice ecosystems, including irrigated lowland, upland, and swampy areas, have been developed and have the potential to be used for biofortification to reduce stunting prevalence in the country. More efforts to improve other important micronutrients such as iron and provitamin A are still needed by using a genetic engineering approach. While food diversification is the best way to overcome malnutrition, rice biofortification through the improvement of the nutritional quality of rice grain has the potential to be a sustainable approach to supplying important nutrition for people who have limited access to a diverse diet. Acceleration of the adoption of healthier rice varieties by farmers is key to getting the maximum benefit from the technologies.